Educational Risk Management to Prevent Stakeholder Decline - Gempur Santoso (Jurnal Multidisiplin Madani, 2024)
In carrying out management education, there is something that is adapted to the culture. This article is inseparable from the educational management paradigm, using educational risk management to prevent a decline in stakeholders. The writing design used in this paper is exposition (descriptive). Explaining risk management to prevent the decline in risk. Various data are taken from several opinions and research results. The conclusion is that there is a crisis of survival of stakeholders and institutional capabilities in the form of uncertainty, inadequate information, weak control, and external observation. Then risk management needs to be carried out to prevent a decline in stakeholders by identifying, measuring and dealing with the causes and consequences of uncertainty in an organization